Autotoxicity in Panax notoginseng of root exudatesand their allelochemicals - Xiang, Wei; Chen, Jianhua; Zhang, Fengyuan; Huang, Rongshao; Li, Liangbo (Frontiers in Plant Science, 2022)
The growth of Panax notoginseng (Burk.) F. H. Chen is frequently hindered due to replanting failure. In the present study, the objective is to determine whether root exudates from P. notoginseng have autotoxicity and identification of allelochemicals from root exudates or rhizosphere soil. We investigated autotoxicity in P. notoginseng using seedling emergence bioassays and hydroponic culture. The allelochemicals in the soils and root exudates were identified with GC-MS, and the autotoxicity of the identified key allelochemicals was investigated by bioassay. The results showed that the root exudates, and extracts from consecutively cultivated soils also showed significant autotoxicity against seedling emergence and growth. In the non-renewed culture solution without activated charcoal (AC), the fresh and dry mass of P. notoginseng tubers of roots was reduced by about half compared to the addition with AC. A total of 44 different components from all samples were defined by GC-MS analyses. Furthermore, the results of multiple statistical analysis showed a t the difference among cultivated soil, uncultivated soil and root exudates. Bioassay of the identified allelochemicals revealed that benzoic acid, phthalic acid, palmitic acid, and stearic acid significantly affected the root growth of P. notoginseng. These substances at 100 μM more significantly decreased the number of lateral roots. Our results demonstrated that autotoxicity results in replant failure of P. notoginseng.